1999
DOI: 10.1046/j.1365-2222.1999.00009.x-i1
|View full text |Cite
|
Sign up to set email alerts
|

Non‐H1‐receptor effects of antihistamines

Abstract: Visit any international allergy meeting and you will soon learn that there are a plethora of very potent and effective histamine H1-receptor antagonists, or antihistamines as they are more often called. Thus, in order to make any particular antihistamine stand out therapeutically or commercially from the others, additional properties, e.g. anti-inflammatory properties, are often claimed. But are these claims valid and, if so, are the 'additional properties' clinically relevant? This document will review the ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 54 publications
1
31
0
Order By: Relevance
“…Histamine as well as DIT decreased the respiratory burst in PMN-leukocytes, suggesting a non-receptor interaction with regulatory enzymes, plasma membrane structure and reduction of the CL signal [5]. The action of H 1 -antagonists may result also in anti-inflammatory activity [1].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Histamine as well as DIT decreased the respiratory burst in PMN-leukocytes, suggesting a non-receptor interaction with regulatory enzymes, plasma membrane structure and reduction of the CL signal [5]. The action of H 1 -antagonists may result also in anti-inflammatory activity [1].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to their antihistamine effects, H 1 -receptor antagonists possess other pharmacological properties that are not uniformly distributed among drugs of this class, such as anti-inflammatory effects [1,2], inhibition of blood platelet functions [3,4] and antioxidant effects [5]. Due to their cationic amphiphilic structure many antihistamines exert a variety of activities, which might result in beneficial side effects.…”
Section: Introductionmentioning
confidence: 99%
“…A series of studies has shown that the second-generation antihistamines possess a series of anti-inflammatory effects in addition to their antagonism of histamine at the H 1 -receptor. 173 To make any particular antihistamine stand out therapeutically or commercially from the other, it is often claimed that these experimental findings are of clinical importance. Such claims with the second-generation antihistamines should indeed be considered within the clinical sphere, and clear added benefit should be evident in relationship to symptomatic outcome measures if such purported anti-inflammatory activity is of relevance.…”
Section: Effect On Nasal Inflammationmentioning
confidence: 99%
“…Depending on their physicochemical properties, they show antiinfl ammatory effects, decrease platelet aggregation and suppress phagocyte activation [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%